Optimizing Workplace Support for Breastfeeding in Female Worker; A Narrative Review - Febriansyah Darus; Ray Wagiu Basrowi; Erika Wasito; Melissa Stephanie Kartjito (ILUNI MKK FKUI and PRODI MKK FKUI, 2023)
Introduction: The increasing participation of women in the labour market has led to a growing trend of female employment. This has a significant impact on women’s roles as mothers, particularly breastfeeding mothers. Objective: This review aims to discuss the benefits and challenges of breastfeeding faced by female workers in the workplace and how to counter itDiscussion: Breastfeeding in the workplace has several advantages for mothers, which may act as an incentive to combine breastfeeding and work. The advantages include reduced absenteeism, increased productivity, and decreased turnover rates. However, breastfeeding in the workplace presents several challenges, including the lack of research on the topic, the lack of support from employers, distance between home and work, the lack of lactation facilities on-site, and reduced milk production during work hours. This situation drives the development of a lactation promotion model that can support breastfeeding in the workplace. The lactation promotion model, comprised of seven major components, can be implemented in the workplace to increase exclusive breastfeeding and boost female worker productivity. Conclusion: It is recommended to give workers with under-6-month children the option of working part-time or returning home earlier and for companies to provide lactation support staff, educational materials, and peer support groups to help working mothers breastfeed at work. The role of company occupational doctors takes a very important place in this lactation promotion model to achieve high breastfeeding rate in female workers.